Earth Biogenome Project: present status and future plans - Gupta, Pushpendra Kumar (Trends in genetics, 2022)
Earth Biogenome Project (EBP) is an ambitious project targeted to provide high-quality reference genome sequences for all 1.8 million named extant (living) eukaryote species. The project was launched on 1 November 2018 with an initial 2 years’ pilot phase (2018–2020) followed by Phase I (2020–2023), during which genomes of 9400 species will be sequenced. The genomes of the remaining ~1.7 million species will be sequenced in a planned manner during Phase II (2024–2027) and Phase III (2028–2030). In view of the excitement generated and the progress already made, the subject was covered in a Special Feature of a recent issue of PNAS (25 January 2022). The present status and future plans of EBP along with challenges faced are briefly discussed in this article. Earth Biogenome Project (EBP) has a target of developing reference genomes of 1.8 million named species by the year 2030 in three phases. It is a network of ~50 networks.The project will make use of emerging next generation sequencing technologies, including both short and long reads.Different aspects of EBP have been covered in nine articles included in a Special Feature of Proceedings of the National Academy of Sciences (PNAS) (25 November 2022).The Office of EBP is located in the Genome Center of the University of California, Davis (UCD); HA Lewin is the Chair with John Kress and Gene Robinson as Co-Chairs. There are eight technical subcommittees to monitor progress of EBP.The output of EBP will facilitate development of methods for conservation, phylogeny and for maintenance of ecological systems.